UAV laser scanning and terrestrial laser scanning point clouds of snow-on and snow-off conditions of a forest plot in the black forest at Hundseck, Baden-Württemberg, Germany [data] - Winiwarter, Lukas; Anders, Katharina; Battuvshin, Guyen; Menzel, Lucas; Höfle, Bernhard (Universität, 2023)
This dataset consists of 3D point clouds acquired via UAV laser scanning (ULS) of a forest plot in the Black Forest in Hundseck, Germany. The plot ...